Investigating the Challenges of Bureaucratic Reform in Developing Countries: A Case Study Approach - Muhdiarta, Untung (Yayasan Ilomata, 2025)
This study examines the challenges encountered during bureaucratic reform in developing countries, focusing on the complexities of implementing effective administrative changes. Employing a qualitative research method that includes a literature review and case study approach, the research highlights the various obstacles governments face, such as resistance to change, lack of institutional capacity, corruption, and political interference. The study identifies common trends and key factors hindering reform efforts by analyzing multiple case studies from different developing nations. A significant finding is the role of entrenched political elites, who often resist changes that may diminish their influence or control over resources. Additionally, weak governance structures and insufficient training programs for civil servants contribute to the slow pace of reform. The study also discusses the importance of fostering a culture of transparency and accountability within public institutions and the need for comprehensive strategies that address both the technical and human aspects of reform. This research contributes to the growing body of literature on public administration reform by providing insights into the multifaceted challenges that developing countries face. It offers recommendations for policymakers to create more adaptable and resilient bureaucratic systems that are better equipped to meet the demands of modern governance.